Yes, we can combine the like terms in the equation.
The like terms in the equation are 2x and x.
Combining them, we get:
2x + x + 3 - 6 = 180
Simplifying further, we have:
3x - 3 = 180
2x + 3 + x - 6 = 180. Can you combine the like terms to simplify the equation?
5 answers
what is x?
To find the value of x, we need to solve the equation:
3x - 3 = 180
Adding 3 to both sides of the equation:
3x = 183
Dividing both sides by 3:
x = 183/3 = 61
Therefore, x = 61.
3x - 3 = 180
Adding 3 to both sides of the equation:
3x = 183
Dividing both sides by 3:
x = 183/3 = 61
Therefore, x = 61.
Now, use the value of x from Part B to fill into the angle (2x + 3) and what do you get? What about when you fill x into the other angle (x - 6)?
To fill in the value of x into the angle (2x + 3), we substitute x = 61:
Angle (2x + 3) = 2(61) + 3 = 122 + 3 = 125 degrees.
To fill in the value of x into the other angle (x - 6), we again substitute x = 61:
Angle (x - 6) = 61 - 6 = 55 degrees.
Angle (2x + 3) = 2(61) + 3 = 122 + 3 = 125 degrees.
To fill in the value of x into the other angle (x - 6), we again substitute x = 61:
Angle (x - 6) = 61 - 6 = 55 degrees.